District level coverage gap in Maternal, Newborn and Child Health care services in India - Rajesh Kumar Rai; Chandan Kumar; Prashant Kumar Singh (Springer, 2019)
India has the highest number of maternal (2010) and child (2009) deaths in the world suggesting a poor coverage in Maternal, Newborn and Child Health (MNCH) care services. This study assessed the coverage gap in MNCH care across districts in India using a robust aggregate Coverage Gap Index (CGI) developed by the 'Countdown 2008 Equity Analysis Group'. The north-south divide in MNCH care coverage gap is apparent. The results derived from this study emphasise the need for focused intervention in 210 districts which have a coverage gap of ⩾50%.